2023
DOI: 10.3171/2023.3.jns23148
|View full text |Cite
|
Sign up to set email alerts
|

Causes of fatal traumatic brain injury in Finland

Abstract: OBJECTIVE The phenotype of patients who suffer fatal traumatic brain injury (TBI) is poorly characterized. The authors examined the external causes, contributing diseases, and preinjury medication in adult patients with fatal TBI in a nationwide Finnish cohort. METHODS Deaths caused by TBIs in Finland were examined among decedents aged ≥ 16 years during 2005–2020 from the national Cause of Death Registry. Usage of prescription medications prior to TBI was studied using medication purchase data from the Socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The frequency of opioid use varied considerably between age groups, with only 4% of patients with fatal TBI younger than 30 years using opioids and 18% of patients older than 90 years. 22 In this study, the strongest association with 30-day mortality was found for strong opioids, second-generation antipsychotics, and atypical antidepressants. There is no comprehensive explanation for why these drugs particularly are so strongly related to fatal TBI.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The frequency of opioid use varied considerably between age groups, with only 4% of patients with fatal TBI younger than 30 years using opioids and 18% of patients older than 90 years. 22 In this study, the strongest association with 30-day mortality was found for strong opioids, second-generation antipsychotics, and atypical antidepressants. There is no comprehensive explanation for why these drugs particularly are so strongly related to fatal TBI.…”
Section: Discussionmentioning
confidence: 54%
“…3 Other possible causes include violence, self-harm, and poisoning. 22 CNS-affecting drugs may predispose or play a role in all these causes. Notably, the interaction between medications and fall risk has been thoroughly studied, particularly in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of traumatic brain injuries (TBI) is slightly above the western European average in Finland, but the TBI mortality is relatively high, suggesting that the injuries may be more severe than they are elsewhere [ 100 , 101 , 102 , 103 , 104 ]. The epilepsy incidence trends among elderly people may also have partially resulted from the increasing incidence of traumatic brain injury in this population [ 102 ], whereas age does not appear to be an independent risk factor for epilepsy after an haemorrhagic stroke in Finnish patients [ 105 , 106 ].…”
Section: Great Unknownsmentioning
confidence: 99%